PENGARUH MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TERHADAP HASIL BELAJAR IPAS MURID KELAS V SDN 09 KOTO BARU - Ilham Asmaryadi, Ahmad; Esa Putri, Sintia; Darniyanti, Yulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes in Science and Social Studies (IPAS) among fifth-grade students at SDN 09 Koto Baru, which were caused by teacher-centered learning that limited students' active participation in asking questions, engaging in discussions, and expressing their opinions. One alternative to overcome this problem is the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model. This study aimed to determine the effect of the STAD cooperative learning model on the IPAS learning outcomes of fifth-grade students at SDN 09 Koto Baru. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The participants consisted of 17 fifth-grade students. Data were collected through pretest and posttest achievement tests and analyzed using the shapiro–wilk normality test and the paired samples t-test with the assistance of SPSS version 25. The results showed that the students' mean score increased from 62.94 on the pretest to 88.24 on the posttest, with a significance value of 0.000 < 0.05. It was concluded that the Student Teams Achievement Divisions (STAD) cooperative learning model had a significant positive effect on improving the IPAS learning outcomes of fifth-grade students at SDN 09 Koto Baru.